Thermodegradation of medium-chain-length Poly(3-hydroxyalkanoates) produced by Pseudomonas Putida from Oleic Acid - Sin, M.C.; Gan, S.N.; Annuar, M.S.M.; Tan, I.K.P. (2010)
Medium-chain-length poly(3-hydoxyalkanoates) (mcl-PHA), comprising six to fourteen carbon-chain-length monomers, are natural thermoplastic polyesters synthesized by fluorescent pseudomonades. In this study, mcl-PHA was produced by Pseudomonas putida from oleic acid in aerobic shake flask fermentation. Thermal degradation of mcl-PHA was performed at temperatures in the range of 160-180 degrees C. Thermodynamic parameters of mcl-PHA thermal degradation were determined where degradation activation energy. E(d) and pre-exponential factor, A equal to 85.3 kJ mol(-1) and 6.07 x 10(5)s(-1), respectively: and exhibited a negative activation entropy (Delta S) of -139.4 J K(-1) mol(-1). Titration was carried out to determine the carboxylic terminal concentration and used to correlate number-average molecular weight (M(n)) of the polymers. Thermally-degraded PHA contained higher amount of carboxylic terminals and lower M(n) compared to the initial PHA and these results coincide with the decreased M(n) in GPC analysis. Thermal properties of initial and degraded mcl-PHA were characterized by thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). The thermal decomposition mechanism was investigated following the analyses of the degradation products using 400-MHz (1)H NMR, FTIR spectroscopy and GC analysis. The overall decomposition reaction is the hydrolysis of ester linkages to produce hydroxyl and carboxylic terminals. A small proportion of unsaturated side chain fragments would undergo oxidative cleavage at C=C linkages, producing minor amount of low-molecular weight esters and acids. At higher temperatures, the hydroxyl terminal can undergo dehydration to form an alkenyl terminal. (C) 2010 Elsevier Ltd. All rights reserved.